PEMBUATAN APLIKASI PENGELOLAAN ALAT DAN BAHAN PADA HARDWARE-RND DEPARTMENT DI PT. SATNETCOM BALIKPAPAN BERBASIS WEB - Muhammad Novit Alldila (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
PT. SatNetCom Balikpapan hardware-RND department involves a lot of tools and materials in every process, but until now the system used to manage equipment and materials for each employee or division is still inefficient, in addition, there are often losses when borrowing tools and materials because there is no data loans that make the data recorded properly. Therefore it requires a system that can manage tools and materials, namely a web-based application that can be a solution in managing and borrowing using the PHP programming language that is devoted to web development and can be embedded in an HTML script, and using a MySQL database as storage of data. This web-based application is expected to be able to overcome the problems that occur in the hardware-RND department so as to facilitate and speed up the process of managing and borrowing tools and materials so that the data is recorded properly.